Wireless optical coupling evaluation in a dielectric resonator nanoantenna - Malheiros-Silveira, Gilliard N. [UNESP]; Hernandez-Figueroa, Hugo E. (Optical Soc Amer, 2018)
A theoretical study regarding wired and wireless link performance by using a dielectric resonator nanoantenna (DRNA) integrated to a metal-dielectric-metal-dielectric (MDMD) nanostrip waveguide is evaluated. Near- and far-field coupling characteristics in receiving (RX) and transmitting (TX) modes of this DRNA are investigated at optical frequencies (C-band). This nanoantenna and its coupling characteristics reveal a promising approach for coupling light to plasmonic nanostrip waveguides and implementing inter-chip communication in nanophotonics using the same or distinct platforms. (C) 2018 Optical Society of America under the terms of the OSA Open Access Publishing Agreement